2005
DOI: 10.1080/00016470510030391
|View full text |Cite
|
Sign up to set email alerts
|

No beneficial effects of joint distraction on early microscopical changes in osteoarthrotic knees

Abstract: We conclude that joint distraction has no beneficial effect on the osteoarthrotic cartilage in papain-induced osteoarthrosis, and nonarticulated distraction worsens the results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 9 publications
0
16
0
Order By: Relevance
“…Karadam et al reported no beneficial effects of distraction on a study using rabbits. 11 On this research, the anatomical and histopathological results show worsening as evaluated by the respective grading and scoring (p < 0.05). Therefore, a significant difference exists between the control and intervention groups though the result was the other way around.…”
Section: Med J Indonesmentioning
confidence: 58%
See 1 more Smart Citation
“…Karadam et al reported no beneficial effects of distraction on a study using rabbits. 11 On this research, the anatomical and histopathological results show worsening as evaluated by the respective grading and scoring (p < 0.05). Therefore, a significant difference exists between the control and intervention groups though the result was the other way around.…”
Section: Med J Indonesmentioning
confidence: 58%
“…Several animal studies show different results. [11][12][13][14] It has only been performed on a pilot study on humans. 15 Some authors also doubt the efficacy of this method.…”
mentioning
confidence: 99%
“…In our study (Karadam et al 2005), non-articulated distraction worsened the results (p = 0.001) whereas articulated distraction had no significant effect (p = 0.1), although the results were worse than the control group. With these data, it is impossible to reach any conclusion other than "there is no beneficial effect of joint distraction on early microscopical changes in osteoarthrotic knees in rabbits, but non-articulated distraction worsens the results".…”
mentioning
confidence: 54%
“…Sir-In the recent publication of Karadam et al (2005) entitled "No beneficial effects of joint distraction on early microscopical changes in osteoarthritic knees; a study in rabbits." the crucial statement is made in the last sentence: "Studies with longer follow-up are necessary because distraction treatment requires up to a year before substantial clinical benefit may be achieved.…”
mentioning
confidence: 99%
“…In a canine study [53] we found beneficial changes in chondrocyte activity immediately after ending the distraction, but no cartilage repair. Karadam and colleagues [54] reported 'no beneficial effects of joint distraction on early microscopical changes in osteoarthritic knees' in a rabbit study. Osteoarthritis was induced by papain injection in 24 rabbits which were divided into four groups.…”
Section: Unloading In Cases Of Severe Osteoarthritis: Joint Distractionmentioning
confidence: 98%